SIKAP KEPATUHAN PASIEN DALAM MINUM OBAT ANTI HIPERTENSI DI WILAYAH KERJA PUSKESMAS - Hasan Nidlom (Bajang Institute, 2024)
Hypertension is an important factor as a trigger for non-communicable diseases such as heart disease, stroke and other cardiovascular diseases which are the cause of many deaths in the world. WHO explains that hypertension contributes to almost 9.4 million deaths from cardiovascular disease every year. Non-adherence problems are commonly encountered in the treatment of chronic diseases that require long-term treatment such as hypertension. Current antihypertensive drugs have been proven to be able to control blood pressure in hypertensive patients, and also play a significant role in reducing the risk of developing cardiovascular complications. However, the use of antihypertensives alone has proven to be insufficient to produce a long-term blood pressure control effect if it is not supported by compliance in using the antihypertensives. This research is a quantitative study using a correlational descriptive design with a cross sectional study approach with a sample size of 43 respondents. The research results show that the variables based on the Chi-Square Test are as follows: Attitude variable (p=0.003). The Health Service needs to increase program development on health and patient compliance behavior in taking anti-hypertension medication by playing an active role in providing education in the community